Witchfinders a seventeenth-century English tragedy - Gaskill, Malcolm (Harvard Univ. Press, 2005)
"By spring 1645, two years of civil war had exacted a dreadful toll upon England. People lived in terror as disease and poverty spread, and the nation grew ever more politically divided. In a remote corner of Essex, two obscure gentlemen, Matthew Hopkins and John Stearne, exploited the anxiety and lawlessness of the time and initiated a brutal campaign to drive out the presumed evil in their midst ... Malcolm Gaskill retells the story of the most savage witch-hunt in English history ... Though their campaign was never legally sanctioned, they garnered the popular support of local gentry, clergy, and villagers ... [This story] serves as a reminder of the power of fear and fanaticism to fuel ordinary people's willingness to demonize others"--Dust jacket.